The role of artificial intelligence in the digital transformation of government: opportunities and ethical challenges - Fan, Youpeng (Frontiers in Public Health, 2025)
This study focuses on the application of artificial intelligence in the digital transformation of government services and the ethical issues that come with it. The research analyzed different paths of global artificial intelligence governance, with a particular focus on the three major frameworks of market-driven, government-guided, and regulatory-led. At the same time, it explored the application of artificial intelligence in government decision support systems, intelligent government services, and governance systems. Research indicates that the transformation empowered by artificial intelligence will bring about four major opportunities: strengthening the decision-making foundation and administrative execution efficiency; Improve the response speed and accuracy of public services; Enhance transparency and promote public participation; Upgrade cross-departmental collaboration through data sharing. The research also involves ethical issues such as algorithmic fairness, privacy and data regulation, definition of autonomous decision-making rights, division of responsibility boundaries, and the digital divide. Based on this, researchers have constructed a complete governance blueprint covering technology policies, regulatory frameworks, and cross-domain stakeholder collaboration, aiming to bridge the cognitive gap between society and technology, alleviate public concerns about public digital services, and balance technological progress and ethical constraints.